ECONOMIC FOUNDATIONS AND FACTORS OF BANKING SYSTEM STABILITY UNDER CONDITIONS OF ECONOMIC INSTABILITY - Ambartsumyan Anastas Alekseyevich; Karimov Diyor Mukhtarovich; Gayratov Akbarali Khurshid ugli (Journals Park Publishing, 2024)
This article discusses the current challenges facing the banking system during periods of economic instability. Economic crises, financial difficulties and global changes create unique conditions for banks, requiring effective strategies and resilience measures. This article analyzes the impact of economic instability on the banking system, identifies the key factors determining the sustainability of banks, and offers practical recommendations to improve its level.
Keywords: banking system, stability, factors, economic instability, financial crises, macroeconomic factors, banking system risks, stabilization measures, strengthening strategies.